2000
DOI: 10.1007/s12043-000-0131-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of two coupled chaotic multimode Nd:YAG lasers with intracavity frequency doubling crystal

Abstract: Abstract. The effect of coupling two chaotic Nd:YAG lasers with intracavity KTP crystal for frequency doubling is numerically studied for the case of the laser operating in three longitudinal modes. It is seen that the system goes from chaotic to periodic and then to steady state as the coupling constant is increased. The intensity time series and phase diagrams are drawn and the Lyapunov characteristic exponent is calculated to characterize the chaotic and periodic regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…view in secure communication [27][28][29][30][31][32][33][34][35][36][37][38]. However, the mode gain reduction occurring in such systems due to nonlinear processes suppresses chaotic dynamics [27].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…view in secure communication [27][28][29][30][31][32][33][34][35][36][37][38]. However, the mode gain reduction occurring in such systems due to nonlinear processes suppresses chaotic dynamics [27].…”
mentioning
confidence: 99%
“…Chaotic synchronization of two such lasers with low values of nonlinear gain reduction factor is achieved and successfully applied for unidirectional optical secure communication [30,31]. A bidirectional coupling of two such lasers is also found to suppress chaotic dynamics [32]. It is recently reported that a negative-delayed optoelectronic feedback is capable of producing chaotic outputs from directly modulated semiconductor lasers with optimum value of nonlinear gain suppression factor [33].…”
mentioning
confidence: 99%
“…Two such lasers are coupled via external electronic coupling [2] whereby the pumping of each laser is modulated according to the output intensity of the other. The rate equations for the coupled system are given by …”
Section: Laser Modelmentioning
confidence: 99%
“…This phenomenon has found many applications in laser dynamics [1][2][3][4], electronic circuits [5,6], chemical and biological systems [7,8] and secure communication [9,10]. Dynamics of an array of coupled systems has also been studied for coupled maps [11][12][13], coupled semi conductor lasers [14], neural networks [15] and in the Josephson junction [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation